대전지역 대기 중 PM2.5의 유기탄소와 원소탄소의 계절별 특성 연구 - 김효선(Hyosun Kim); 정진상(Jinsang Jung); 이진홍(Jinhong Lee); 이상일(Sangil Lee) (한국대기환경학회지(국문), 2015)
To investigate the seasonal variations of carbonaceous aerosol in Daejeon, OC (organic carbon), EC (elementalcarbon) and WSOC (water soluble organic carbon) in PM2.5 samples collected from March 2012 to February 2013were analyzed. PM2.5 concentrations were estimated by the sum of organic matter (1.6×OC), EC, water-solubleions (Na+, NH4+, K+, Mg2+, Ca2+, Cl-, SO42-, NO3-). The estimated PM2.5 concentrations were relatively higher inwinter (29.50±12.04 μg/m3) than those in summer (13.72±6.92 μg/m3). Carbonaceous aerosol (1.6×OC+EC) wasa significant portion (34~47%) of PM2.5 in all season. The seasonally averaged OC and WSOC concentrations wererelatively higher in winter (6.57±3.48 μgC/m3 and 4.07±2.53 μgC/m3 respectively), than those in summer (3.07±0.8 μgC/m3, 1.77±0.68 μgC/m3, respectively). OC was correlated well with WSOC in all season, indicating thatthey have similar emission sources or formation processes. In summer, both OC and WSOC were weakly correlatedwith EC and also poorly correlated with a well-known biomass burning tracer, levoglucosan, while WSOC is highlycorrelated with SOC (secondary organic carbon) and O3. The results suggest that carbonaceous aerosol in summerwas highly influenced by secondary formation rather than primary emissions. In contrast, both OC and WSOC inwinter were strongly correlated with EC and levoglucosan, indicating that carbonaceous aerosol in winter wasclosely related to primary source such as biomass burning. The contribution of biomass burning to PM2.5 OC andEC, which was estimated using the levoglucosan to OC and EC ratios of potential biomass burning sources, wasabout 70±15% and 31±10%, respectively, in winter. Results from this study clearly show that PM2.5 OC hasseasonally different chemical characteristics and origins. KCI Citation Count: 8